2016
DOI: 10.20524/aog.2016.0033
|View full text |Cite
|
Sign up to set email alerts
|

Real-time elastography as a noninvasive assessment of liver fibrosis in chronic hepatitis C Egyptian patients: a prospective study

Abstract: BackgroundHepatitis C virus is a worldwide problem. Noninvasive methods for liver fibrosis assessment as ultrasound-based approaches have emerged to replace liver biopsy. The aim of this study was to evaluate the diagnostic accuracy of real-time elastography (RTE) in the assessment of liver fibrosis in patients with chronic hepatitis C (CHC), compared with transient elastography and liver biopsy.MethodsRTE, FibroScan and liver biopsy were performed in 50 CHC patients. In addition, aspartate aminotransferase to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…In our study we depended on Transient Elastography in the assessment of liver fibrosis as it was proved to be a reliable method to detect significant fibrosis compared to histological assessment of liver tissue [14,18], it measures liver stiffness based on the propagation speed of shear waves with overall diagnostic accuracy reaching 94% [19].…”
Section: Discussionmentioning
confidence: 99%
“…In our study we depended on Transient Elastography in the assessment of liver fibrosis as it was proved to be a reliable method to detect significant fibrosis compared to histological assessment of liver tissue [14,18], it measures liver stiffness based on the propagation speed of shear waves with overall diagnostic accuracy reaching 94% [19].…”
Section: Discussionmentioning
confidence: 99%
“…In our study we used FibroScan in the assessment of liver fibrosis as it was proved to be a reliable method to detect significant fibrosis compared to histological assessment of liver tissue [14,19], it measures liver stiffness based on the propagation speed of shear waves with overall diagnostic accuracy reaching 94% [20].…”
Section: Discussionmentioning
confidence: 99%
“…Specificity and sensitivity could reach above 90% [13]. Mobarak et al indicated that TE had higher diagnostic value than other examination methods for diagnosis of liver fibrosis progression and cirrhosis [14]. TE measures the degree of liver fibrosis accurately and can play an important role in predicting complications of advanced compensated chronic liver disease (cACLD), such as gastroesophageal varices, portal hypertension, cirrhosis, and HCC [15].…”
Section: Clinical Applicationmentioning
confidence: 99%